Efikasi Bioinsektisida Bacillus thuringiensis Barliner terhadap Gryllus bimaculatus De Geer (Orthoptera: Gryllidae) pada Tanaman Padi Utama dan Ratun - Khoirul Ikhsanudin Hanif; Siti Herlinda; Suwandi Suwandi; Tili Karenina (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Hanif et al, 2017. Efficacy of Bacillus thuringiensis Barliner Bioinsecticide against Â Gryllus bimaculatus De Geer (Orthoptera: Gryllidae) in Major Rice Crops and Ratooning Rice. JLSO 6(1):95-105. Crickets (Gryllus bimaculatus) are an important pests on rice that can reduce productivity. The application of Bacillus thuringiensis bioinsecticide is expected to be an alternative methode to control these pest. The objective of the study was to investigate optimal dose of B. thuringiensis in suppressing rice damage was caused by G. bimaculatus. The observation were conducted on rice cultivation in Pelabuhan Dalam Village, Pemulutan Subdistrict of Ogan Ilir Regency. The results showed that application of B. thuringiensis bioinsecticide had significant effects in suppressing rice crop damage by G. bimaculatus, but did not had significant effect on growth of rice plants.